Pengembangan media pembelajaran pop up book digital pada pembelajaran PJOK - Ningsih, Yuni Fitriyah; Hariadi, Nopi; Sugeng, Imam; Kandupi, Ardiansyah D; Utomo, Andri Wahyu; Bimantoro, Apriliyan Putra (Jurnal Porkes, 2023)
The problem with this research is the lack of media use in the physical education learning process for children, making children easily bored and bored. This study aims to find out the results of the development and find out the results of validation and the effectiveness of developing digital pop up book learning media in PJOK class IV SD learning. This type of research uses a qualitative approach. The research method used is development research. The total population in this study was 41. The sample of this study was students of class IVA and IVB. The level of validity that has been carried out by the validator is that it reaches a value of 94.75% with a very decent category, indicating that the learning media is very good in terms of validity and can be relied upon in its use. The effectiveness of learning outcomes in the cognitive domain of students using learning media materials shows 77.8%. The results of the student response test got a score of 88 in the very good category. The conclusion of this study can improve students' conceptual understanding, students' fine motor skills, motivation, and student learning outcomes. In addition, the digital pop-up book learning media also received a positive response from students